LABORATORY INVESTIGATION OF A NEW LIBYAN CHEMICAL EOR: Impact of GWLI on Relative Permeability, Wettability, Oil Recovery, Breakthrough and Fractional Flow - Madi Abdullah Naser (Journal of Earth Energy Engineering, 2019)
The greater demand for crude oil, the increased difficulty of discovering new reservoirs, and the desire to reduce dependence on imports have emphasized the need for enhanced recovery methods capable of economically producing the crude remaining in known reservoirs. Oil recovery from oil reservoirs may be improved by designing the composition and salinity of water injection. The process is sometimes referred to as sea or smart water injection. In this paper, a Gaberoun Water Leak Injection (GWLI) have been discovered and investigated as a new Libyan chemical EOR in laboratories on relative permeability, wettability, oil recovery, breakthrough, and fractional flow for carbonate and sandstone reservoirs. GWLI has several advantages which are relatively cheap, reliable, and available. GWLI potentially would have a wide range of applications in water injection such as wettability alteration. The equipment and the operating procedures were designed to simulate the reservoir condition. The experimental results indicate that, that the GWLI has caused the increasing of oil recovery in sandstone and carbonate core. The impact of GWLI on oil recovery in sandstone core samples was higher than carbonate core samples. The effect of acidity (pH) of GWLI on oil recovery in sandstone and carbonate core samples was higher when the pH is 5 than when the acidity is 10. Hopefully, the research findings can possibly be useful for references and for operating companies as an important source for understanding and visualizing the effects of pH, permeability, porosity, and wettability on oil recovery in reservoir rock using GWLI.